Guía de actividades lúdicas para la estimulación de la lecto escritura en niños de 5 a 10 años dirigida a maestros/as hospitalarios - Granizo Granizo, Lorena Paola (2015)
Child development 5 to 10 years - Hospital Education - Literacy and development - recreational Guide to stimulate literacy in children 5 to 10 years activities aimed at teachers and hospital teachers - Conclusions - Recommendations - References List - attachments - historical evolution of language.